Assessment of Seismic Demand and Damping of a Reinforced Concrete Building After CFRP Jacketing of Columns - KOÇAK, PINAR İNCİ; Göksu, Çağier; Töre, Erkan; Binbir, Ergun; Ateş, Ali Osman; İlki, Alper (Techno-Press, 2022)
While the lateral confinement provided by an FRP jacket to a concrete column is passive in nature, confinement is activated when the concrete expands due to additional compression stresses or significant shear deformations. This characteristic of FRP jacketing theoretically leads to similar initial stiffness properties of FRP retrofitted buildings as the buildings without retrofit. In the current study, to validate this theoretical assumption, the initial stiffness characteristics, and thus, the potential seismic demands were investigated through forced vibration tests on two identical full-scale substandard reinforced concrete buildings with or without FRP retrofit. Power spectral density functions obtained using the acceleration response data captured through forced vibration tests were used to estimate the modal characteristics of these buildings. The test results clearly showed that the natural frequencies and the mode shapes of the buildings are quite similar. Since the seismic demand is controlled by the fundamental vibration modes, it is confirmed using vibration-based full-scale tests that the seismic demands of RC buildings remain unchanged after CFRP jacketing of columns. Furthermore, the damping characteristics were also found similar for both structures.
Keywords: CFRP; Forced Vibration Test; Reinforced Concrete; Retrofitting; Seismic Demand